Blockade of Cannabinoid CB1 receptor attenuates the acquisition of morphine-induced conditioned place preference along with a downregulation of ERK, CREB phosphorylation, and BDNF expression in the nucleus accumbens and hippocampus. (6th September 2016) - Zhang, Jianbo; Wang, Na; Chen, Bo; Wang, Yi'nan; He, Jing; Cai, Xintong; Zhang, Hongbo; Wei, Shuguang; Li, Shengbin
Highlights: Morphine-induced CPP but not NO-CPP elevated CB1R expression both in the NAc and hippocampus. AM251 attenuated morphine-induced CPP and CB1R expression in the NAc and Hippocampus. CB1R mediated downstream ERK-CREB-BDNF signaling is implicated in morphine reward. Abstract: Cannabinoid CB1 receptor (CB1R) is highly expressed in the mesocorticolimbic system and associated with drug craving and relapse. Clinical trials suggest that CB1R antagonists may represent new therapies for drug addiction. However, the downstream signaling of CB1R is not fully elucidated. In the present study, we investigated the relationship between CB1R and the extracellular signal-regulated kinase (ERK), cAMP response element-binding protein (CREB), brain-derived neurotrophic factor (BDNF) signaling in the nucleus accumbens (NAc) and hippocampus in morphine-induced conditioned place preference (CPP), which is used to assess the morphine-induced reward memory. The protein level of CB1R, ERK, CREB, and BDNF were detected by western blotting. Additionally, a CB1R antagonist, AM251, was used to study whether blockade of CB1R altered the CPP and above-mentioned molecules. We found an increase of CB1R expression in the NAc and hippocampus of the mice following morphine CPP, but not those after repeated morphine in home cage without context exposure (NO-CPP). Both morphine CPP and NO-CPP induced an upregulation of ERK, CREB phosphorylation and BDNF expression. Furthermore, pretreatment with AM251 before morphine attenuated the CPP acquisition and CB1R expression as well as the activation of ERK-CREB-BDNF cascade. Collectively, these findings demonstrate that (1) Repeated morphine with context exposures but not merely the pharmacological effects of morphine increased CB1R expression both in the NAc and hippocampus. (2) CB1R antagonist mediated blockade of ERK-CREB-BDNF signaling activation in the NAc and hippocampus may be an important mechanism underlying the attenuation of morphine CPP.